ZmSPL10/14/26 are required for epidermal hair cell fate specification on maize leaf. Issue 4 (24th March 2021) - Kong, Dexin; Pan, Xuan; Jing, Yifeng; Zhao, Yongping; Duan, Yaping; Yang, Juan; Wang, Baobao; Liu, Yuting; Shen, Rongxin; Cao, Yingying; Wu, Hong; Wei, Hongbin; et al.
Summary: The epidermal hair and stomata are two types of specialized structures on the surface of plant leaves. On mature maize leaves, stomatal complexes and three types of hairs are distributed in a stereotyped pattern on the adaxial epidermis. However, the spatiotemporal relationship between epidermal hair and stomata development and the regulatory mechanisms governing their formation in maize remain largely unknown. Here, we report that three homologous ZmSPL transcription factors, ZmSPL10, ZmSPL14 and ZmSPL26, act in concert to promote epidermal hair fate on maize leaf. Cytological analyses revealed that Zmspl10/14/26 triple mutants are completely glabrous, but possess ectopic stomatal files. Strikingly, the precursor cells for prickle and bicellular hairs are transdifferentiated into ectopic stomatal complexes in the Zmspl10/14/26 mutants. Molecular analyses demonstrated that ZmSPL10/14/26 bind directly to the promoter of a WUSCHEL ‐related homeobox gene, ZmWOX3A, and upregulate its expression in the hair precursor cells. Moreover, several auxin‐related genes are downregulated in the Zmspl10/14/26 triple mutants. Our results suggest that ZmSPL10/14/26 play a key role in promoting epidermal hair fate on maize leaves, possibly through regulating ZmWOX3A and auxin‐related gene expression, and that the fates of epidermal hairs and stomata are switchable.